A Hybrid of a CBT- and a CAT-based New English Placement Test Online (NEPTON) - Papadima-Sophocleous, Salomi (My University, 2008)
In recent years, many tertiary institutions have been changing their pen-and-paper English placement test practices into computer based ones. In the process of constructing the University of Nicosia (Intercollege) New English Placement Test Online (NEPTON), we discovered how to redesign our test to include the use of technology. The present article reports this experience in three parts. In the first section, we demonstrate how NEPTON, a hybrid of a computer-based test (CBT) and a computer adaptive test (CAT) model was influenced and shaped by theoretical issues such as CBT and CAT characteristics--their advantages and disadvantages--and by practical issues such as the particular context of the institution. This is followed by a detailed description of the test, highlighting its essential and innovative features. Lastly, we discuss and analyze different aspects of the test's first administration to establish how reliable and valid this test is as a placement instrument for first-year University of Nicosia (Intercollege) students.
Keywords: New English Placement Test Online (NEPTON); Hybrid of a Computer-based Test (CBT); English Placement Test (EPT); Foreign Language Placement Testing